Dating Endometriotic Ovarian Cysts Based on the Content of Cyst Fluid and its Potential Clinical Implications. (July 2015) - Guo, Sun-Wei; Ding, Ding; Shen, Minhong; Liu, Xishi
This study was undertaken to test the hypotheses that, due to gradual accumulation of dead erythrocytes and their ingested products resulting from repeated hemorrhage, older endometriomas (whitish in color) contain chocolate fluid with higher iron content than younger (brownish/blackish in color) ones with concomitant higher collagen content and more adhesions. We recruited 30 premenopausal women with histologically confirmed ovarian endometriomas and collected samples of their endometriotic lesions and chocolate fluid and measured the viscosity, density, and the concentration of total bilirubin, ferritin, and free iron of the chocolate fluid. We also evaluated the lesion color and adhesion scores. In addition, we performed Masson trichrome and Picro-Sirius red staining on all endometriotic cysts and evaluated the extent of fibrosis in the lesions. We found that fluids taken from white-colored endometriomas had significantly higher concentration of total bilirubin, ferritin, and free iron, respectively, than black/brown-colored ones. In addition, older cysts had fluids that had significantly higher density and viscosity. Fluid density correlated positively with the concentrations of total bilirubin, ferritin, and free iron. Older lesions had significantly more collagen content and higher adhesion scores. Taken together, these data supports the notion that older cysts, having experienced more bleeding episodes, contain chocolate fluid that is higher in viscosity, density, and iron content and higher fibrotic content than younger ones. This provides another piece of evidence that endometriotic lesions are wounds that undergo repeated injury and repair, resulting ultimately fibrotic lesions that are resistant to hormonal treatment.